Contemporary drummer + one - WECKEL, Dave (DCI usic video inc, 1987)
Garden wall, Spur of the moment, Island Magic, Again and Again, Rainy day, Pretty girls, Love me alittle bit, Sport car jingle, angel fire and though the lens, drum and cymbal set-up